A STYLISTIC STUDY OF THE SPEECHES OF SOME KEY ACTORS OF THE ‘JUNE 12’ CRISIS IN NIGERIA (1993-1998) (2005)
This study examines the roles played by language in the conflict generated by the annulment of the June 12, 1993 presidential election in Nigeria (commonly referred to as ‘June 12, 1993). ‘June 12’ crisis is so significant in Nigeria’s democratization process that the way it is played out in linguistic and non-linguistic terms deserves scholarly attention. However, extant literature on the conflict pays little attention to the manipulations of language. This study explores that various ways that language is used in defending and promoting personal and group interests, and in subverting the opponent’s goals. The study is limited ti the written mode of the speeches made by the key actors in the conflict, namely Ibrahim Babangida, Sani Abacha and M.K.O. Abiola. Twenty speeches made by these key actors which focus primarily on the ‘June 12’ crisis are used in the study. Out of this number, seven are from Ibrahim Babangida, seven from Sani Abacha and six from M.K.O. Abiola. The study employs descriptive and comparative analytical methods, which account for how linguistic and non-linguistic features merge, differ or subvert others. To provide an adequate theoretical orientation, it applies a revised version of the Hallidayan systematic functional linguistic theory, whose major strength lies in its recognition of the fact that texts are produced and received in contexts of situation. The study reveals that the discourse dwells largely on the tacit trading on ideology as each of the speaking strives to justify his own cause in the conflict while to criminalize his opponents. Also, M.K.O. Abiola at some point almost begins to adopt military speech style, especially in the uses of coercion in responding to the military. Strategies such as appeal to credibility, vilification of opponents, and creations of impressions about the pursuit of unity and common purpose, which are common to political speeches, also feature in the speeches. On the whole, the speaker’s manipulations of meaning have implications for political communication in Nigeria. First, meaning becomes a contested site in which the audience may easily be defrauded. The staging of power, ideology, and double-speak at the meaning sacrifices ‘truth’ and undermines mutual responsibility, the spirit of nation-building, and national reconciliation. The study thus opens up a crucial area that the national reconciliation project in Nigeria should address: the reconciliation of ethnic and national interests and the differentiation of personal from group pursuits. Further research also needs to be carried out on how the ‘June 12’ discourse has influenced inter-ethnic communicative exchanges in Nigeria, as well as the roles of the media in the conflict. The study indicates the need for stylisticians to be interested in discourses that present urgent societal problems.